Design of millidevices to expedite apparent solubility measurements. Issue 9 (17th June 2022) - Pons Royo, Maria del Carme; Beulay, Jean-Luc; Valery, Eric; Jungbauer, Alois; Satzer, Peter
Abstract : A fast, automated and accurate millidevice for determination of the apparent solubility of proteins and impurities and different industrially relevant precipitating agents. Abstract : Protein solubility is a critical attribute in the development and production of monoclonal antibodies. Available solubility data refer to pure solutes which do not consider solvents and impurities which have a significant effect on solubility. Thus, solubility curves need to be determined experimentally. Previously established methods to determine the apparent solubility of proteins are based on manual assays which are time-consuming and labor-intensive. We present the design of simple and adaptable millidevices for fast solubility curve determination. Such a device in the form of a tubular reactor was manufactured from polymethylmethacrylate by laser cutting. The reactors had multiple injection points for the precipitant that allowed a controlled and precise addition of the precipitating agent at different concentrations. Hence, antibodies could be directly harvested at different concentrations of precipitating agents. The simple and flexible design allowed the number of pumps required to be reduced to only one for each solution and the distribution of the precipitating agent at different concentrations without valves. To demonstrate the wide applicability of the prototype in determining solubility curves, we used 2 industrially relevant precipitating agents, PEG6000 and ZnCl2, to measure the apparent solubilities of 4 antibodies and CaCl2 to measure the apparent solubility curves for dsDNA. In all cases, the data obtained were consistent between the device and manual assays with good reproducibility. This millidevice can be used for fast characterization of protein solutions such as solubility, degradation or stability of the antibodies under different conditions.